Raman Spectroscopic Investigation on TiO2–N719 Dye Interfaces Using Ag@TiO2 Nanoparticles and Potential Correlation Strategies. Issue 10 (3rd July 2013) - Qiu, Zhi; Zhang, Meng; Wu, De‐Yin; Ding, Song‐Yuan; Zuo, Qi‐Qi; Huang, Yi‐Fan; Shen, Wei; Lin, Xiao‐Dong; Tian, Zhong‐Qun; Mao, Bing‐Wei
Abstract Herein, we employ Ag@TiO2 core–shell nanoparticles for surface‐enhanced Raman scattering (SERS) investigations of TiO2–N719 dye interfaces. In situ electrochemical SERS investigations of the Ag@TiO2–N719 interaction are systematically carried out under a series of electrode‐potential controls. By comparing the potential dependence of resonant and pre‐resonant SERS spectra recorded with different laser excitations, bidentate carboxylate linkage is considered to be involved in N719 adsorption on TiO2. Meanwhile, SCN ligand shows obvious interactions with TiO2, and their role in the adsorption and orientation of N719 on TiO2 should not be underestimated. The in situ SERS spectra of Ag@TiO2 show a clear bell‐shaped intensity–potential relation for the major bands of N719. A molecule‐to‐TiO2 charge‐transfer resonance is tentatively attributed to account for such a phenomenon. Under the influence of such a charge‐transfer resonance, valuable information about the N719–TiO2 interaction as well as the intramolecular deformation of N719 is obtained.